The Mediating Role Of Rumination In Breakup Distress After Romantic Relationships And Sleep Disturbance Of The Students And A Five- Day- Proposed Intervention Program (Journal of Namibian Studies : History Politics Culture, 2023)
Post-breakup distress and its aftermath have been of interest to international researchers for nearly two decades. However, this issue has not received adequate attention from the scientific community in Vietnam. Therefore, the objective of this study is to explore the relationship between post-breakup distress and sleep difficulties in university students through the mediating role of rumination. Hence, recommendations for future research and appropriate interventions for the issue can be suggested in order to provide effective coping strategies for university students. Based on the results of the study, a five-day intervention program is developed for those who are disturbed by rumination and breakup distress resulting to sleep issues.The study utilized a mixed-method approach with a total of 170 university students across Ho Chi Minh City. Precisely, 164 participants were asked to complete a quantitative survey (online or paper-based form) and the other 8 participants were directly interviewed about their last romantic relationship experiences. The results supported the initial hypothesis that rumination plays a mediating role in the relationship between the level of post-breakup distress and sleep difficulties among students. Additionally, our research group discovered that underlying factors contributing to the level of post-breakup distress included the duration of the relationship and the individual's active-passive stance when receiving the breakup event.